2004
DOI: 10.7748/ns.19.6.33.s60
|View full text |Cite
|
Sign up to set email alerts
|

The research agenda for protocol-based care

Abstract: Protocols provide great potential to deliver best practice. However, questions remain about the benefits of protocol-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The construction of the framework was informed by the funder's requirement, an initial review of the literature undertaken for the proposal [6], and key policy developments. The study's theoretical framework integrates various components, including the four areas that play a role in protocol-based care and related impact on stakeholder outcomes: patients, staff, organisations, and policy makers:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of the framework was informed by the funder's requirement, an initial review of the literature undertaken for the proposal [6], and key policy developments. The study's theoretical framework integrates various components, including the four areas that play a role in protocol-based care and related impact on stakeholder outcomes: patients, staff, organisations, and policy makers:…”
Section: Resultsmentioning
confidence: 99%
“…However, in practice, practitioners are rarely bound to follow guidelines, protocols, and standards, and so 'rules' may not necessarily be a defining feature of protocol-based care per se . Because of this lack of clarity, we used protocol-based care as an umbrella term, which encompassed the use of a number of different care processes aimed at standardisation, including protocols, guidelines, care pathways, and algorithms that were being used in service delivery at the time of the study [6,7]. When we embarked on the study, it was unclear whether protocol-based care would be something greater than the sum of its parts [8].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals are obliged to work according to evidence‐based practice, which implies basing clinical decisions on integrated knowledge from the best available science, clinical experience, contextual circumstances and patients' requirements . This can be challenging in clinical contexts where complex problems involve series of related actions and decisions . Due to advances in understanding pathophysiology, innovations in supportive technology and an aging population, the field of intensive care is expanding in all western countries at a high cost .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, protocol‐based care can provide a useful support to healthcare professionals, facilitate evidence‐based practice, improve patient care, reduce time with mechanical ventilation, decrease length of stay and imply cost savings . However, because the development and use of care protocols differ between settings and countries, there is a need for international knowledge sharing with regard to development, implementation and evaluation of the phenomenon .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hospital staff believe SCPs increase their ability to provide high-quality patient care (Lee 2005, 2006, Dahm & Wadensten 2008, P€ oder et al 2011, Svensson et al 2012, Bjurling-Sj€ oberg et al 2013, Jakobsson & Wann-Hansson 2013. SCPs may also help staff improve patient outcomes, reduce length of hospital stays, and enhance teamwork and record keeping (Rycroft-Malone et al 2004, Deneckere et al 2013, Deng et al 2014. Furthermore, a Cochrane review including 27 studies concluded that use of SCPs is associated with reduced hospital complications and improved documentation .…”
Section: Introductionmentioning
confidence: 99%